Digital transformation through multi-device HBIM workflow: a case study on supporting the adaptive reuse of the Odd Fellows Building in Atlanta, Georgia - Li, Botao; Willkens, Danielle S. (Frontiers in Built Environment, 2026)
This paper presents a multi-device scan-to-HBIM workflow developed for the adaptive reuse of the Odd Fellows Building (b.1911), a socially significant historic landmark with seven stories above ground and a basement, located in Atlanta’s Sweet Auburn National Historic Landmark District. As a major contributing structure within the culturally significant corridor, the building’s adaptive reuse demands precise documentation, rapid data collection, and efficient stakeholder communication. To meet these goals within strict time and funding limits, the research integrates Terrestrial Laser Scanning (TLS), Matterport 360-camera technology, and Unmanned Aerial Vehicles (UAVs) to create an efficient and accessible pipeline for documenting historic buildings, assisting with renovation and construction processes. TLS is employed as a benchmark capture method to establish a baseline point cloud for aligning all other data. Matterport technology enables fast interior scanning while providing high-resolution visuals and an interactive virtual tour platform. UAVs are deployed to supplement data collection in hard-to-access exterior areas, especially where ground-based reality capture tools encounter spatial or logistical barriers. This not only accelerates data acquisition under time and budget constraints but also offers stakeholders the ability to remotely revisit the space without geographic limitation. This multi-device strategy optimizes the trade-off between capture speed and spatial tolerance, accommodating a complex mix of preserved historic elements (exterior and lobby space) and altered upper floors. Besides, a full TLS capture approach could cause potential data saturation and processing inefficiencies. The multi-device approach has multiple data processed registered to provide one combined point cloud, which is integrated into a semantically rich HBIM model developed in Autodesk Revit at Level of Development (LoD) 300. Although not a full Digital Twin (DT), the resulting model establishes a foundational framework for future digital twinning and immersive applications. By demonstrating how different reality capture technologies can be effectively integrated to accommodate site limitations, stakeholder needs, and funding constraints, this case study contributes to the broader discourse on digital transformation in construction, particularly the evolving intersection of BIM, remote visualization, and the early stages of DT development in the preservation sector.